Maximal Convergence of Faber Series in Morrey-Smirnov Spaces - كنج, أحمد (Latakia University Journal -Basic Sciences Series, 2023)
Let be a finite, simply connected domain in the complex plane bounded by a regular closed curve . It is known that any function analytic in can be expanded into a Faber series of the form , where are Faber series coefficients and are Faber polynomials. In this work, the maximal convergence properties of the partial sums of the Faber series in the Morrey-Smirnov spaces , , of analytic functions defined on are investigated.